PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, KOMPLEKSITAS OPERASI PERUSAHAAN DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR - Dewi Ariyani, Ni Nyoman Trisna (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Companies that have gone public in general will issue financial statements in accordance with a predetermined time. However, there are still some companies that experienced a delay in issuing the financial statements. Delay in issuing financial statements that have been audited by independent auditors is one indication that the company experienced a problem. The purpose of this study was to determine the effect of profitability, firm size, complexity of operations and the firm's reputation on audit report lag. The type of data used is quantitative data and qualitative data. Quantitative data in the form of audited financial statements in 2010-2012 manufacturing companies listed on the Indonesia Stock Exchange and qualitative data in the form of a list of companies manufacturing the period 2010-2012 are listed in Indonesia Stock Exchange and the independent auditor's report. To determine the sample in this study using purposive sampling method, with a total of 162 samples were obtained by the company. The results of this study showed variable profitability, firm size, complexity of operations and the firm's reputation affect the audit report lag.
Keywords: Audit Report Lag; Profitabilitas; Ukuran Perusahaan; Kompleksitas Operasi Perusahaan; Reputasi KAP